2022
DOI: 10.1021/acs.jafc.1c06981
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Determination of 12 Lactones and 11 Volatile Phenols in Nongrape Wines through Headspace-Solid-Phase Microextraction (HS-SPME) Combined with High-Resolution Gas Chromatography-Orbitrap Mass Spectrometry (GC-Orbitrap-MS)

Abstract: This paper clarifies the contribution of lactones and volatile phenols to the aroma of nongrape wine. A target method for the simultaneous determination of these two kinds of volatiles in nongrape wines was developed using headspace-solid-phase microextraction (HS-SPME) combined with high-resolution gas chromatography-Orbitrap mass spectrometry (GC-Orbitrap-MS). A high-resolution mass spectrometry database including 12 lactones and 11 volatile phenols was established for qualitative accuracy. Different matrix-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 50 publications
(130 reference statements)
0
9
0
Order By: Relevance
“…However, indoles are emitted naturally from many sources, including flowers, vertebrate hosts, and oviposition sites of microbiotic origin, suggesting they influence multiple behaviors across species [ 81 , 82 ]. AaegOR6 responded best to 4-chromanone, a compound that is found in shrubs of the Asteraceae family, is structurally related to quinolines, and is a key constituent of flavonoid skeletons [ 83 , 84 ]. AaegOR10 responded to 3-methylindole (skatole) found in animal feces and produces behavioral responses in other Dipteran species [ 85 88 ], while AaegOR55 responded to the structurally related compounds 2,3-dimethylindole and 3-methylindole.…”
Section: Discussionmentioning
confidence: 99%
“…However, indoles are emitted naturally from many sources, including flowers, vertebrate hosts, and oviposition sites of microbiotic origin, suggesting they influence multiple behaviors across species [ 81 , 82 ]. AaegOR6 responded best to 4-chromanone, a compound that is found in shrubs of the Asteraceae family, is structurally related to quinolines, and is a key constituent of flavonoid skeletons [ 83 , 84 ]. AaegOR10 responded to 3-methylindole (skatole) found in animal feces and produces behavioral responses in other Dipteran species [ 85 88 ], while AaegOR55 responded to the structurally related compounds 2,3-dimethylindole and 3-methylindole.…”
Section: Discussionmentioning
confidence: 99%
“…AaegOR responds to 4-chromanone, of which there is little literature regarding its occurrence in natural settings. However, it is a key element of flavonoid skeletons [59]. AaegOR10 responds to 3-methylindole (skatole), which is found in animal feces and produces behavioral responses in other Dipteran species [6063].…”
Section: Discussionmentioning
confidence: 99%
“…However, indoles are emitted naturally from many sources, including flowers, vertebrate hosts, and oviposition sites of microbiotic origin, suggesting they influence multiple behaviors across species [7172]. AaegOR6 responds best to 4-chromanone, a compound that is found in shrubs of the Asteraceae family, is structurally related to quinolines and is a key constituent of flavonoid skeletons [7374]. AaegOR10 responds to 3-methylindole (skatole) found in animal feces and produces behavioral responses in other Dipteran species [7578].…”
Section: Discussionmentioning
confidence: 99%
“…Each analysis was performed in duplicate (Y. Liu et al, 2022 ). The retention indices were obtained by injection of the C6–C24 n -alkane series (Supelco, Bellefonte, PA, USA) mixture under the same chromatographic conditions.…”
Section: Methodsmentioning
confidence: 99%
“…We recently used GC-Orbitrap-MS to analyze aroma compounds in fruit wines ( Lin et al, 2022 ; R. Liu, Liu, Zhu, Kortesniemi, Zhu, & Li, 2022 ; Y. Liu et al, 2022 ). Similarly, high-resolution and sensitive instruments were found that could identify more key volatiles in foods such as green tea, fruits and wines ( Lim et al, 2020 , Qian et al, 2020 , Yang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%